Water Adsorption Kinetics of Rice Bran Derived Bioplastic as Candidate for Edible Food Packaging Material - Istianah, Nur; Prastiwi, Wahyu Intan; Amalia, Fania Dewi; Ike, Ratri (Program Studi Teknologi Pangan, 2023)
Plastic food packaging is being an environmental issue and the development of edible plastic is urgently needed. This work is aimed to perform the kinetics of water adsorption of the bio-plastic that is essential properties for the reuse application. Edible plastic was invented from the combination of rice bran and alginate(2:1 w/w) by using glycerol as plastsizer. With the thickness of 0.14mm it has tensile strength of 1.3N and elasticity of 4%(m/m). Its water adsorption kinetic was evaluated at the immersion temperature of 10, 30, and 60°C using Langmuir equation. The result showed that the edible plastic has maximum water adsorption capacity 94.34(g/g) at 30°C immersion temperature and 96.15%(g/g) at 10°C and 60°C. The high water adsorption capacity induce the possibility of edible plastic reuse for food material through immersion or cooking.